The Setting of Communal Spaces in an Apartment through the Indonesian Architectural Regionalism Approach in Kampung Keputran Pasar Kecil, Surabaya - Herson Jaya Chandra; Rony Gunawan Sunaryo; Maria Immaculata Hidayatun (Advances in Civil Engineering and Sustainable Architecture, 2019)
The aim of the study is to identify the ideal layout of communal spacesin an apartment through the design approach of Indonesian architecturalregionalism in kampung. Kampung Keputran Pasar Kecil in Surabaya is the locusof study. The relocation of the kampung to vertical houses, which are not suitableto the cultural context of life in kampung. This problem then leads to thedisappearace of some places in kampung-lifestyle’s identities and decreases thequality of social and economic life of the apartment’s habitants. Qualitativeanalysis by the identification and reinterpretation of spaces’ and places’ valuesare used as the research methods which the form of elements of spaces and placesrequired, based on the needs of the habitants of kampung; then spacesconceptualizing in accordance to the regionalism context of kampung andauthorized regulations; and design simulation is done based on kampungexistence as the final result of the study.